Regional Differences in Diffuse Idiopathic Skeletal Hyperostosis: A Retrospective Cohort Study from Sweden and Japan. Issue 24 (15th December 2018) - Hirasawa, Atsuhiko; Robinson, Yohan; Olerud, Claes; Wakao, Norimitsu; Kamiya, Mitsuhiro; Murotani, Kenta; Deie, Masataka
Abstract : Study Design: We retrospectively reviewed computed tomography (CT) records of patients in Japan and Sweden, which are both aging populations. Objective: To research the influence of ethnicity and region on diffuse idiopathic skeletal hyperostosis (DISH) prevalence. Summary of Background Data: DISH can complicate non-surgical treatment of spinal fractures and often requires surgical intervention. We previously reported a prevalence of DISH in Japan that was higher than that reported in other studies. Methods: We retrospectively reviewed CT records of patients in Japan and Sweden, which have both aging populations. Patients undergoing whole body CT during trauma examinations at an acute outpatient clinic in Uppsala University Hospital in a 1-year period were eligible for inclusion. Excluded were those less than 40 and more than or equal to 90 years old, and those with previous spinal surgery. The prevalence of DISH by sex and age was determined according to radiographic criteria by Resnick. Results from Sweden were compared with the Japan data, which we previously reported. Results: Age of the eligible subjects (265 men and 153 women) ranged from 40 to 89 years, with a mean age of 63.4 years. Among men, 86 (32.5%) were diagnosed with DISH, and the results by age (40s, 50s, 60s, 70s, and 80s) were: 6 (10.7%), 13 (22%), 35 (46.1%), 17 (34%), and 15 (62.5%) patients, respectively. Among women, 16 (10.5%) had DISH, and the results by age were as follows: 1 (2.6%), 1 (3.3%), 2 (6.7%), 6 (22.2%), and 6 (22.2%) patients, respectively. These results did not differ from those previously published for Japan (Fisher exact test, men: P = 1, 0.27, 0.12, 0.06, and 1, respectively; women: P = 0.49, 0.62, 0.5, 0.8, and 0.3, respectively). Conclusion: The presented cohort study revealed that ethnicity and region may not be notable factors of DISH prevalence, since patients from both Japan and Sweden had similar DISH prevalence. Level of Evidence: 3